Peningkatan Produktivitas Mesin Adroit S-90 Dengan Pendekatan Nilai Overall Equipment Effectiveness (OEE) Pada Produksi Tissue (Studi Kasus di PT. Etica Sari Pratama Tangerang) - Hartono, Hartono; Hadi, Lukman (Journal Industrial Manufacturing, 2022)
PT. Etica Sari Pratama is an industry engaged in the health industry, namely wet wipes. The problems currently experienced at PT. Etica Sari Pratama is the result of low productivity, during the wet tissue production process which results in decreased production. Improvements are made to increase the productivity results on the production line. Thus, the above problems must be immediately followed up, so that productivity results can achieve results according to predetermined targets by evaluating the performance of production facilities at the company's Adroit S-90 machine is causing production to be interrupted or stopped. Therefore, an analysis of the factors resulting from decreased productivity is carried out. Improvements must be made to increase productivity. And knowing the results of productivity, problem solving is done using the Overall Equipment Effectiveness, fishbone and why-why analysis method. It can be seen that after making improvements to the comparative data from January to June the productivity had an average value of 78% and after making improvements from July to December it had an average value of 97%. Has an increase of 19%. Keywords: production line, productivity, overall equipment effectiveness, why-why analysis, fishbone.